Before humanity: posthumanism and ancestrality - Herbrechter, Stefan (Critical Posthumanisms, 2022)
Before Humanity takes up the question of the post- in the posthuman from the position of ancestrality. Speculating about who or what comes after the human inevitably throws us back to our very beginnings. The before in Before Humanity in this context takes on two meanings: 1) what happened before we apparently became human? - which translates into a critical reading of paleo-anthropology, as well as evolutionary narratives of hominization; 2) living through the end of a certain (humanist, anthropocentric) notion of humanity, what tasks lie before us? - which provokes a critical reading of the Anthropocene and current narratives of geologization. In other words, Before Humanity investigates conceptualizations of humanity and asks whether we have ever been human and if not, what could, or maybe what should we have been?